1987
DOI: 10.1016/s0735-1097(87)80198-5
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography detects tissue metabolic activity in myocardial segments with persistent thallium perfusion defects

Abstract: Positron emission tomography with 13N-ammonia and 18F-2-deoxyglucose was used to assess myocardial perfusion and glucose utilization in 51 myocardial segments with a stress thallium defect in 12 patients. Myocardial infarction was defined by a concordant reduction in segmental perfusion and glucose utilization, and myocardial ischemia was identified by preservation of glucose utilization in segments with rest hypoperfusion. Of the 51 segments studied, 36 had a fixed thallium defect, 11 had a partially reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
7

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(49 citation statements)
references
References 41 publications
2
39
1
7
Order By: Relevance
“…[5][6][7][23][24][25] PET is a non-invasive tool for evaluating myocardial metabolism, as well as myocardial perfusion, in vivo. 19,20 In the present study, focal or diffuse fasting FDG uptake, which strongly suggested anaerobic metabolism, was observed in all 24 patients and to our knowledge, this is the first clinical report demonstrating that the fasting FDG uptake by the myocardium is significantly increased in syndrome X. The lower ejection fraction of the left ventricle in patients with diffuse FDG uptake relative to that in patients with focal uptake suggests causal consequences between alteration of the myocardial metabolism and ventricular function.…”
Section: Myocardial Metabolism In Syndrome Xsupporting
confidence: 60%
See 1 more Smart Citation
“…[5][6][7][23][24][25] PET is a non-invasive tool for evaluating myocardial metabolism, as well as myocardial perfusion, in vivo. 19,20 In the present study, focal or diffuse fasting FDG uptake, which strongly suggested anaerobic metabolism, was observed in all 24 patients and to our knowledge, this is the first clinical report demonstrating that the fasting FDG uptake by the myocardium is significantly increased in syndrome X. The lower ejection fraction of the left ventricle in patients with diffuse FDG uptake relative to that in patients with focal uptake suggests causal consequences between alteration of the myocardial metabolism and ventricular function.…”
Section: Myocardial Metabolism In Syndrome Xsupporting
confidence: 60%
“…More recently, the development of positron emission tomography (PET) has resulted in better evaluation of the coronary microcirculation and metabolic condition of the myocardium. [19][20][21][22] Based on these facts, the present study was designed to assess myocardial metabolism by PET using F-18 fluorodeoxyglucose (FDG), and to characterize the small vessels histopathologically in an endomyocardial biopsy in order to investigate the pathophysiology of syndrome X.…”
mentioning
confidence: 99%
“…[1][2][3][4] By the conventional resting glucose-loaded methodology, FDG uptake in normal myocardium is enhanced, so the tracer is seen in all viable tissue, and the glucose avidity of postischemic myocardium may be hidden. In contrast, with fasting protocols, increased FDG uptake is associated with postischemic or hibernating myocardium, whereas normal tissue is characterized by very low FDG uptake.9"10 Thus, use of the fasting methodology in this study permitted analysis of the level of FDG activity within areas where perfusion had been restored after revascularization.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As an alternative to`01T1 scintigraphy, metabolic imaging using positron emission tomography (PET) also may be used for the detection of viable myocardium. 3,[15][16][17][18][19] In particular, the identification of viable myocardium from PET studies is based on the presence of either normal '8fluorodeoxyglucose (FDG) uptake or FDG: blood flow mismatch,15 whereas the identification of viable myocardium from`01T1 scintigraphy is based on the presence of either normal`'TI uptake or reversiblè "Tl defects (after either redistribution or reinjection). "1 The accuracy of these criteria to predict an improvement in regional function after revascularization has been evaluated, for both PET and`'Tl scintigraphy with rest-reinjection, in a relatively small number of patients.3,1'"'2 '19 The results of these studies indicate that the current PET and 2"T1 criteria used to identify viable myocardium are quite accurate but not perfect, as they may underestimate viability in up to 22% of the myocardial segments classified as nonviable.…”
mentioning
confidence: 99%